The impact of primary schools’ inclusiveness on the inclusion of students with autism spectrum disorder - Šilc, Mateja; Lavrič, Miran; Schmidt, Majda (Frontiers in Education, 2024)
The inclusion of students with autism spectrum disorder (ASD) is a complex issue for schools. This study investigates the impact of the inclusivity of Slovenian primary schools on the inclusion of their students with ASD. We postulated that each pedagogical dimension of inclusion (i.e., academic, social, and emotional inclusion) of students with ASD would demonstrate a positive correlation with each dimension of inclusiveness of primary schools (i.e., inclusive culture, policy, and practice). Forty regular Slovenian elementary schools participated in the research. The Perceptions of Inclusion Questionnaire was completed by 200 respondents (40 students with ASD, 40 parents, 120 teachers), and the Index for inclusion by 240 respondents (40 parents, 200 school professionals). The analysis revealed one significant correlation, a weak positive correlation between inclusive practice and academic inclusion. Multiple regression analyses also identified one conditionally substantial pair. When we excluded the inclusive culture and policy and only considered the control of demographic variables, the results showed that the increase in inclusive practices corresponds to the increase in academic inclusion. The absence of correlations between the dimensions of school inclusivity and the pedagogical dimensions of including students with ASD can be attributed to the lack of systemic solutions for accommodating a diverse student population and the failure to conduct a thorough analysis of the inclusion and implementation of whole-school approaches. However, the Slovenian adaptation of the Index for Inclusion, a promising tool, offers hope in addressing these challenges.